(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The article examines current trends in the development of the global market of military-technical products. The author draws attention to the steady growth dynamics of purchases of military-industrial products in the world. The article describes key global trends in the development of promising innovative developments of dual-use goods. Since the end of the Cold War, global military research and development (R & D) has found itself in a situation of declining demand for its products. During this period, there was a reduction in military spending in the former Soviet Union and in many other countries. The United States of America has become the undisputed leader in the global market of the military-industrial complex (MIC). The author analyzed the dynamics of us spending in the late 1990s and early 2000s and showed in tables the increase in the gap in spending on the US military-industrial complex and the rest of the world. The article says that some of the civilian R & D is funded from private sources, because large companies have sufficient budgets to finance R & D. In general, the differences between civilian and military production lines have decreased – there is a trend of dual use of products. The author emphasizes that due to the increase in the share of civilian R & D, military R & D has undergone major structural changes in most countries. The study tracks changes in customer priorities in the military-industrial sector, the emergence of new, relevant products and services. The article examines the current trend of involving civilian producers in the development of Defense and security policies, cooperation with defense institutions and non-governmental organizations. The dynamism of scientific and technological progress requires monitoring the competitive positions of national producers in the military-industrial complex sector. The article also analyzes promising areas and key future trends in the development of the global military-industrial complex market.